In vivo estimation of the Young's modulus in normal human dermis - Saavedra A.C. (2018)
Skin elastic properties change during a cutaneous disorder or in the aging process. Deep knowledge of skin layers helps monitoring and diagnosing structural changes. High frequency ultrasound (HF-US) has been recently introduced to diagnose and evaluate some dermatological disorders in the clinical practice. US elastography adds elasticity information of the analyzed tissue. In particular, harmonic elastography estimates the speed of shear waves produced by external vibration sources, in order to relate the shear wave speed to the Young's modulus. In the epidermis and dermis layers, shear waves are not generated; in contrast, surface acoustic waves (SAWs) exist as they propagate in the top of the tissue. This study uses crawling wave sonoelastography for the estimation of SAWs in human thigh dermis in vivo. Experiments were performed in ten volunteers in the range of 200 - 500 Hz. As other studies suggest, SAW speed needs to be compensated to reach shear wave speed, for calculating the Young's modulus. Thus, the SAW speed estimated was corrected when it propagates in solidUS gel interface. Specifically, the elasticity modulus found was 18.35 ± 1.04 KPa for a vibration frequency of 200 Hz. Results suggest that the elasticity modulus can be estimated in vivo using crawling wave HF-US for skin application and shows potential for future application in skin disorders. © 2018 IEEE.